Tissue engineering with chondrocytes and function of the extracellular matrix: (review) - Gößler, Ulrich; Hörmann, Karl; Riedel, Frank (International journal of molecular medicine, 2004)
Tissue engineering represents a promising method for the construction of autologous chondrogenic grafts for reconstructive surgery. The destruction or malformation of organs such as nasal cartilage, pinna and trachea in otorhinology-head and neck surgery can be caused by both: primary disease or treatment modalities. A large part of modern medical practice is aimed to repair, replace, maintain or enhance the function of damaged or diseased tissues and organs. Replacement or repair is by either artificial implants or transplantation of tissues. Such interventions are hindered by factors such as rejection by the immune system, limited blood supply or morbidity of the donor site. Reconstruction of an injured face using plastic surgery is a prime example of when the limitations of materials, science and reconstructive techniques become apparent. This review aims to briefly outline the use of chondrocytes for tissue engineering with special regard to the function of the extracellular matrix for the signalling between the chondrocytes.